PLL Frequency Stability Enhancement Under Weak Grid Considering Reactive Current Support - Bin Hu; Ling Zhan; Heng Nian; Donglian Qi (CES Transactions on Electrical Machines and Systems)
The phase-locked loop (PLL) plays an essential role for synchronizing renewable power generation to the grid. However, as per the grid-code compliance for reactive current support, the PLL output frequency fluctuates significantly and exceeds the limitation, which seriously threaten the safe supply of electricity. In this paper, the underlying theoretical mechanism and dominant force behind the maximum PLL frequency deviation are revealed. Accordingly, two feasible approaches are proposed to enhance the PLL frequency stability with validations in experimental results.